Water immersion - Wawryków, Agata; Korabiusz, Katarzyna; Fabian-Danielewska, Anna; Wawryków, Paweł (Journal of Education, Health and Sport, 2017)
Water immersion is one of the methods of birth used since antiquity. Although it requires adequate facilities and trained medical personnel, it is an increasingly popular alternative to the classical form of labor. It brings many benefits for both emerging and newborn. However, proper examination is necessary in order to qualify to water birth taking into account any contraindications.